If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 = 5(x + 5) + 3 Reorder the terms: 4 + 6x = 5(x + 5) + 3 Reorder the terms: 4 + 6x = 5(5 + x) + 3 4 + 6x = (5 * 5 + x * 5) + 3 4 + 6x = (25 + 5x) + 3 Reorder the terms: 4 + 6x = 25 + 3 + 5x Combine like terms: 25 + 3 = 28 4 + 6x = 28 + 5x Solving 4 + 6x = 28 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + 6x + -5x = 28 + 5x + -5x Combine like terms: 6x + -5x = 1x 4 + 1x = 28 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + 1x = 28 + 0 4 + 1x = 28 Add '-4' to each side of the equation. 4 + -4 + 1x = 28 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 28 + -4 1x = 28 + -4 Combine like terms: 28 + -4 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| x+33-21=13 | | 2x^2+17xy+21y^2= | | 2xy^2+6xy-56x=0 | | x+33-21= | | 0.5x-1.5=2.6x+2.2 | | 16x^2-8x-3= | | y+6=5y-4 | | y+6=4y+2 | | 55x^2+7x-6= | | 4(6x+30)=96 | | -6x+7=4x-23 | | 2x+10=2y | | 1.72-0.04=0.42 | | 7x+3=5x+25 | | -10+7x=-3x-80 | | 6x-3=-30+3x | | 500=150+20w | | 5x-9=3x+7 | | 264-5x=40x+19 | | 7y^2-14y+15=114 | | -6+2/7=x | | 14x^2-53x+14= | | -2x+7=-25+2x | | x-42=3 | | (5x-3)*(x-3)=252 | | -6+2/7 | | 3T-4T-4=3T-6 | | 6x-6=18+2x | | 3TY-4T-4=3T-6 | | 14x+8=32 | | 6x-6=182x | | 6(x-9)-7=24x-133 |